Abiotic mediation of a mutualism drives herbivore abundance. (13th November 2015) - Mooney, Emily H.; Phillips, Joseph S.; Tillberg, Chadwick V.; Sandrow, Cheryl; Nelson, Annika S.; Mooney, Kailen A.
Abstract: Species abundance is typically determined by the abiotic environment, but the extent to which such effects occur through the mediation of biotic interactions, including mutualisms, is unknown. We explored how light environment (open meadow vs. shaded understory) mediates the abundance and ant tending of the aphid Aphis helianthi feeding on the herb Ligusticum porteri . Yearly surveys consistently found aphids to be more than 17‐fold more abundant on open meadow plants than on shaded understory plants. Manipulations demonstrated that this abundance pattern was not due to the direct effects of light environment on aphid performance, or indirectly through host plant quality or the effects of predators. Instead, open meadows had higher ant abundance and per capita rates of aphid tending and, accordingly, ants increased aphid population growth in meadow but not understory environments. The abiotic environment thus drives the abundance of this herbivore exclusively through the mediation of a protection mutualism.